Psychological well-being in students of the University of Havana - Cruz Xenes, Massiel María (2020)
The research aimed to characterize psychological well-being in university students, from the positive psychology and the multidimensional perspective. Its general objective was to characterize the psychological well-being in third-year students of the University of Havana, in the 2018-2019 academic year. The study was descriptive-correlational, with a mixed methodology. Interviews with typical subjects and the BIEPS-A Adult Psychological Well-being Scale were applied. It was obtained as a result that the psychological well-being of the students obtained a medium level, there are no interactions between this category and the sociodemographic variables collected in the study. As a conclusion, it was obtained that the affected dimensions of well-being were Autonomy and Situation Control / Self-acceptance. However, the tendencies of satisfactory expression related to the affective bonds towards family, friends and partner; as well as the achievement of Life Projects focused on the professional sphere.